A Systematic Literature Review on Career Adaptability among Adolescents - Anita Cristy; Farida Kurniawati (Yayasan Keluarga Guru Mandiri, 2023)
The topic of career is one of the hottest topics that still need to be updated, especially in education. Each student's career needs to be explored starting from their teens and even at an early age. According to Jean Piaget (2002), the stages of adolescent development begin at the age of 11/12 years to 18/20 years before entering early adulthood. Middle school, including junior high school, senior high school, or vocational school, and the initial semester of entering college is the age range in this systematic literature review. This study aims to know the factors that influence the career adaptability of adolescents in the Asia context. This study used a qualitative systematic literature review to analyze 13 articles with various research methods, such as quantitative, longitudinal, and intervention research, as well as the validation of career adaptability tools in the context of adolescence and education. The findings show that career adaptability among adolescents can be affected by internal and external factors. From the findings, it can be concluded that in the ASIA context, teachers and parents have a role in building career adaptability, and each country has different characteristics of career adaptability. This study provides suggestions regarding future research on career adaptability studies for adolescents.